Risky Business? Manufacturer and Retailer Action to Remove Per- and Polyfluorinated Chemicals From Consumer Products. (August 2019) - Cousins, Elicia Mayuri; Richter, Lauren; Cordner, Alissa; Brown, Phil; Diallo, Sokona
In the absence of comprehensive environmental regulation, under what conditions can social movement pressure on the private sector generate substantive change? We explore this question in relation to per- and poly-fluoroalkyl substances (PFAS), a class of persistent, bioaccumulative, and toxic chemicals that are widely used in consumer products and industrial processes yet remain largely understudied and weakly regulated. This paper focuses on the strengths and limitations of one high-profile shame campaign by Greenpeace that has called for clothing and outdoor brands to eliminate PFAS from their products. We find that while the campaign appears to have spurred widespread awareness of PFAS in the apparel industry, corporate action remains fragmented and leaves broader environmental and social justice concerns unaddressed. We highlight the urgent need for comprehensive federal regulation for toxic chemicals, increased funding for green chemistry, and collaborative governance of global production networks.